Vasoactive intestinal peptide-oma causing refractory diarrhea in a young woman. Issue 4 (8th June 2020) - Shankar, Nagasri; Linzay, Catherine; Rowe, Kyle
Abstract: Vasoactive intestinal peptide (VIP)–secreting neuroendocrine tumors are an exceptionally rare cause of chronic diarrhea. We describe a 36-year-old woman presenting with a 2-year history of severe diarrhea and electrolyte derangements ultimately diagnosed with VIPoma.